ARTS mediates apoptosis and regeneration of the intestinal stem cell niche. Issue 1 (December 2018) - Koren, Elle; Yosefzon, Yahav; Ankawa, Roi; Soteriou, Despina; Jacob, Avi; Nevelsky, Alexander; Ben-Yosef, Rahamim; Bar-Sela, Gil; Fuchs, Yaron
Abstract Stem cells (SCs) play a pivotal role in fueling homeostasis and regeneration. While much focus has been given to self-renewal and differentiation pathways regulating SC fate, little is known regarding the specific mechanisms utilized for their elimination. Here, we report that the pro-apoptotic protein ARTS (aSeptin4 isoform) is highly expressed in cells comprising the intestinal SC niche and that its deletion protects Lgr5+ and Paneth cells from undergoing apoptotic cell death. As a result, theSept4/ ARTS−/− crypt displays augmented proliferation and, in culture, generates massive cystic-like organoids due to enhanced Wnt/β-catenin signaling. Importantly, Sept4/ ARTS−/− mice exhibit resistance against intestinal damage in a manner dependent upon Lgr5+ SCs. Finally, we show that ARTS interacts with XIAP in intestinal crypt cells and that deletion ofXIAP can abrogateSept4/ ARTS−/− -dependent phenotypes. Our results indicate that intestinal SCs utilize specific apoptotic proteins for their elimination, representing a unique target for regenerative medicine. The mechanisms regulating intestinal stem cell elimination remain unclear. Here, the authors identify that the pro-apoptotic protein ARTS (aSeptin4 isoform) interacts with XIAP in the intestinal stem cell niche to regulate stem cell survival during intestinal homeostasis and regeneration.